2003
DOI: 10.1046/j.0143-2885.2003.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary analysis of the morphology of lateral canals after root canal filling using a tooth-clearing technique

Abstract: The modified tooth-clearing technique allowed observation of fine morphological details in all specimens. Effective gutta-percha filling was evident in most of the wide coronal lateral canals whilst the apical narrow ramifications were often incompletely filled by cement. Overall AH-Plus demonstrated better diffusion into lateral accessory canals compared to Pulp Canal Sealer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
2
64
0
6
Order By: Relevance
“…In clinical conditions, the use of a sealer may further enhance the flow of filling materials into the lateral canals of the root canal system. The use of human teeth rendered transparent by a decalcification and clearing protocol described by Venturi et al 18 allowed three-dimensional internal visualization of the root canal filling within the simulated lateral canals, and complemented the radiographic analysis. 22 The results of the present study showed that both analyses (3D visualization and radiography) had similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical conditions, the use of a sealer may further enhance the flow of filling materials into the lateral canals of the root canal system. The use of human teeth rendered transparent by a decalcification and clearing protocol described by Venturi et al 18 allowed three-dimensional internal visualization of the root canal filling within the simulated lateral canals, and complemented the radiographic analysis. 22 The results of the present study showed that both analyses (3D visualization and radiography) had similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The working length (WL) was established by subtracting 1mm from the entire length. After the root canals were prepared, the teeth were subjected to a tooth decalcification and clearing procedure using a technique described by Venturi et al 10,18 First, the specimens were decalcified in a solution of 5% hydrochloric acid (Hexis Científica S/A, Jundiaí, Brazil), which was changed every 24 hours for approximately 5 days, until the teeth became rubber-like in texture. Afterwards, #8 and #10 K-files were inserted through the labial and lingual root surfaces at 2, 5, and 8 mm from the WL up to the main root canal, creating the simulated lateral canals.…”
Section: Methodsmentioning
confidence: 99%
“…The diameter of the lateral canal was created by using engine driven reamer size 15, which was compatible with size of lateral canals (0.15mm) reported in previous study (13). Using this approach, it Radiographic evaluation, clearing techniques or both methods have been used to identify the amount of filling achieved in lateral canals in natural teeth (7,9,10,14). Clark & Eldeeb (15) reported that filled lateral and accessory canals on cleared teeth did not always appear on radiographic images.…”
Section: Discussionmentioning
confidence: 99%
“…26 Kök kanal dolgusunun kalitesinin değerlendirilmesinde kök dentinin şeffaflaştırılması alternatif bir yöntemdir. 27 Radyografi de kök kanal dolgularının değerlendirilme-sinde kullanılabilir.…”
Section: Kök Kanal Dolgusunun Değerlendirilmesiunclassified